Targeting peptide‐enhanced antibody and CD11c+ dendritic cells to inclusion bodies expressing protective antigen against ETEC in mice. Issue 2 (15th October 2018) - Jiang, Xinpeng; Xia, Shuang; He, Xinmiao; Ma, Hong; Feng, Yanzhong; Liu, Ziguang; Wang, Wentao; Tian, Ming; Chen, Heshu; Peng, Fugang; Wang, Liang; Zhao, Peng; et al.
ABSTRACT: Enterotoxigenic Escherichia coli (ETEC) remains a massive burden in developing countries with increasing morbidity and mortality rates; it is also an important pathogen in the farming industry and is a leading cause of bacterial diarrhea. Our previous study showed that nanometer‐sized inclusion bodies (IBs) of the fimbrial adhesin subunit protein (FaeG), mutation heat‐stable enterotoxin a (mSTa), heat‐labile enterotoxin b (LTb), and STb (nontargeting) fusion protein as an oral vaccine induced both systemic and mucosal immune responses. In this study, to enhance the protective efficacy to ETEC, we used Yersinia enterocolitica adhesive and M‐cell‐targeting peptides to analyze high‐efficiency antigen‐specific immune presentation in the gut. Here, we showed that immunization with the IBs of ETEC—FaeG‐mSTa‐LTb‐STb—induced a specific systemic and mucosal immune response in the gut, whereas the combination of both targeting peptides resulted in the highest titer, protective immune response against ETEC. A lymphocyte proliferation assay has shown that the IBs induced immunologic memory. The specific antibody of the targeting groups could effectively neutralize toxins, thereby protecting the cells of the small intestine and reducing the level of cAMP and cGMP, and the groups with double targeting showed the best effect. The most important finding was that the targeting peptides stimulate the T helper (Th ) cells through Th 17 and Th l and that Th l cells dominated the cellular immune response. We found that the targeting peptide could also activate CD11c + on lymphoid dendritic cells, which processed and presented antigens to T cells through Th 1‐mediated IFN‐γ and IL‐12, thereby enhancing the antibody titers. The double‐targeting peptide had a better effect on stimulating the immune cells to enhance the antibody titers.—Jiang, X., Xia, S., He, X., Ma, H., Feng, Y., Liu, Z., Wang, W., Tian, M., Chen, H., Peng, F., Wang, L., Zhao, P., Ge, J., Liu, D. Targeting peptide‐enhanced antibody and CD11c+ dendritic cells to inclusion bodies expressing protective antigen against ETEC in mice. FASEB J. 33, 2836–2847 (2019). www.fasebj.org